Investigating the Impacts of UVC Radiation on Natural and Cultured Biofilms: An assessment of Cell Viability - Cierra R. Braga; Kailey N. Richard; Harrison Gardner; Geoffrey Swain; Kelli Z. Hunsucker (Microorganisms, 2023)
Biofilms are conglomerates of cells, water, and extracellular polymeric substances which can lead to various functional and financial setbacks. As a result, there has been a drive towards more environmentally friendly antifouling methods, such as the use of ultraviolet C (UVC) radiation. When applying UVC radiation, it is important to understand how frequency, and thus dose, can influence an established biofilm. This study compares the impacts of varying doses of UVC radiation on both a monocultured biofilm consisting of Navicula incerta and field-developed biofilms. Both biofilms were exposed to doses of UVC radiation ranging from 1626.2 <semantics>mJ/cm2</semantics> to 9757.2 <semantics>mJ/cm2</semantics> and then treated with a live/dead assay. When exposed to UVC radiation, the N. incerta biofilms demonstrated a significant reduction in cell viability compared to the non-exposed samples, but all doses had similar viability results. The field biofilms were highly diverse, containing not only benthic diatoms but also planktonic species which may have led to inconsistencies. Although they are different from each other, these results provide beneficial data. Cultured biofilms provide insight into how diatom cells react to varying doses of UVC radiation, whereas the real-world heterogeneity of field biofilms is useful for determining the dosage needed to effectively prevent a biofilm. Both concepts are important when developing UVC radiation management plans that target established biofilms.